Analisis Motivasi Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Ilir Barat II Kota Palembang - Muhammad Ilham; Wita Farla WK (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to analyze the influence of work motivation on the performance of employees at the Ilir Barat II District Office, Palembang City. This research uses a quantitative approach by applying simple regression analysis. The population in this study was 58 civil servant employees at the Ilir Barat II District Office, Palembang City, so the sample in this study was the entire population of civil servant employees at the Ilir Barat II District Office, Palembang City, totaling 58 respondents. The data used in this research is primary data obtained from individuals through questionnaires and measured using a Likert scale. Based on the results of the hypothesis analysis (t test), it was concluded that work motivation had a positive and significant effect on the performance of employees at the Ilir Barat II District Office, Palembang City.